Effect of hemodialysis on extracellular vesicles and circulating submicron particles - Ruzicka, Marcel (BMC Nephrol, 2019)
BACKGROUND: Although hemodialysis is a highly effective treatment for diffusive clearance of low molecular weight uremic toxins, its effect on circulating extracellular vesicles and submicron particles is less clear. The purpose of this study was to examine the impact of hemodialysis on circulating levels of submicron particles. METHODS: Plasma samples from patients were collected immediately before and after the mid-week hemodialysis session. Total submicron particles were assessed by nanoparticle tracking analysis and levels of endothelial (CD144(+)), platelet (CD41(+)), leukocyte (CD45(+)), and total (Annexin V(+)) membrane microparticles (MPs) were assessed by flow cytometry. RESULTS: Total submicron particle number was significantly lower post-dialysis with reductions in particles < 40 nm, 40–100 nm, and 100–1000 nm in size. Circulating annexin V(+) MPs, platelet MPs, leukocyte MPs, and endothelial MPs were all reduced following dialysis. Assessment of protein markers suggested that extracellular vesicles were not present in the dialysate, but rather adsorbed to the dialysis membrane. CONCLUSIONS: In summary, hemodialysis is associated with reductions in circulating submicron particles including membrane MPs. Accordingly, there may be significant interdialytic variation in circulating submicron particles. Investigators interested in measuring extracellular vesicles in patients undergoing hemodialysis should therefore carefully consider the timing of biosampling.